Factors Influencing Farmers' Decisions in Implementing Hydroponic Systems in Paprika Farming in Tutur District, Pasuruan Regency - Nuriah Yuliati; Ika Sari Tondang; Eko Nurhadi (Nusantara Science and Technology Proceedings, 2023)
A foreign vegetable commodity that has the potential to be developed in Indonesia and has a high economic potential is paprika. Based on data from the Badan Pusat Statistik for the last 5 years, it can be seen that in East Java paprika production has fluctuated in harvest area and production yields. Tutur District is one of the sub-districts located in Pasuruan Regency, which is one of the largest paprika producing areas in East Java. Some farmers in managing their farming already use a hydroponic system. Hydroponic systems have higher risks and costs compared to conventional systems in their management. In Tutur District, farmers use hydroponic systems and conventional systems. This shows that in choosing a planting system farmers have certain reasons. There are factors that influence farmers' decisions in implementing a hydroponic system. The objectives of this research are: (1) Describe the characteristics of farmers implementing hydroponic and conventional paprika cultivation systems, (2) Analyze the factors that influence farmers' decisions in implementing a hydroponic system in paprika farming in Tutur District, Pasuruan Regency. The research was carried out in Tutur District starting in January-February 2023. The technique for collecting respondents in this research used the Census method, namely the entire population was sampled. The data obtained were analyzed using descriptive analysis methods and logistic regression analysis. The results of the research show that the factors that influence farmers' decisions in implementing a hydroponic system in paprika farming are age, farming experience, farming income, participation in farmer groups.